The Role of Village Government In Overcoming Environmental Pollution Caused by Tofu Factory Waste - Muhammad Andri; Mohammad Rafie; Haris Budiman; Afif Ilanul Huda (Universitas Kuningan, 2023)
Environmental problems cannot be separated from human activities themselves which cause damage to nature and has very broad consequences for human and animal life. Environmental damage is caused by a business that is only concerned with profits, ignoring the consequences of its production which can pollute the surrounding environment. The research method used by the author in studying this problem is normative juridical. using a statutory approach. The problem that occurred in this study was the emergence of a pungent odor and damage to the irrigation river ecosystem caused by this tofu factory waste. And there is no business permit or environmental permit from the tofu factory. The issues raised are 1. What is the role of the Village Government in dealing with environmental pollution caused by this factory waste? 2. What are the Pesa Government's efforts regarding environmental pollution caused by tofu factory waste. In conducting this research the authors used a normative juridical research method. The results showed that the role of the village government in overcoming environmental pollution caused by tofu factory waste generally has 3 roles, namely as a facilitator, motivator, and mediator. Such responsibility is limited to a formal existence. However, it must still refer to the provisions stipulated in Law Number 32 of 2009 concerning PPLH and Regional Regulation 11 of 2019 concerning the Nganjuk PPLH. Permits are a juridical instrument used by the government as a system for managing conditions in people's lives that must be obeyed by all people to control activity so that their business has strong legality. By completing a business permit and environmental permit, the business complies with the law